Cultural Heritage Documentation and Conservation: Three-Dimensional (3D) Laser Scanning and Geographical Information System (GIS) Techniques for Thematic Mapping of Facade Stonework of St. Nicholas Church (Pisa, Italy). Issue 1 (2nd January 2016) - Lezzerini, Marco; Antonelli, Fabrizio; Columbu, Stefano; Gadducci, Renzo; Marradi, Alessandro; Miriello, Domenico; Parodi, Luca; Secchiari, Lorenzo; Lazzeri, Andrea
ABSTRACT: This article reports the mapping of the stones, including marbles and brick masonry, used for building the facade of the medieval Church of St. Nicholas (XI centuryad ), one of the most interesting churches in Pisa, due also to the nearby famous octagonal bell tower. Mapping of stone materials was performed using a computer-aided design (CAD)/geographical information system (GIS) software package for storing and processing spatial information of the ashlars, obtained using three-dimensional (3D) laser-scanning data, combined with high-resolution images, and stone-to-stone observations. Based on collected data, the facade of the Church of St. Nicholas appeared mostly composed of rocks belonging to the metamorphic Tuscan sequence, quartzites, and marbles from Mt. Pisano area. Other types of rocks were also observed, as black limestones quarried at some kilometers northwest from Pisa in the Monti d'Oltre Serchio area, white Apuan marbles and Macigno sandstones. Conversely, intarsia appeared mainly made up of serpentinite and, subordinately, red limestones laid in white Apuan and Mt. Pisano marbles.